REFORMASI UNDANG-UNDANG KELUARGA ISLAM DI MALAYSIA: SATU ANALISIS TERHADAP GAGASAN KONSEP FIQH SEMASA - Abd Rahim, Rahimin Affandi (Jurnal Syariah, 2008)
Basically, this article focuses upon reforms of the Muslim family law in Malaysia. In order to achieve such objective, it is constructed to be consisted into three different sections, namely; first, an introduction concerning the urgent need for the improvement of the Muslim family law in Malaysia; second, an exposition of the distinctive component of the recent Muslim family law in Malaysia, in term of pre-marriage and after marriage stage and finally it will follow with the summary and conclusion.